[Gd(AAZTA)]− Derivatives with n‐Alkyl Acid Side Chains Show Improved Properties for Their Application as MRI Contrast Agents. Issue 5 (28th December 2020) - Kock, Flávio Vinicius Crizóstomo; Forgács, Attila; Guidolin, Nicol; Stefania, Rachele; Vágner, Adrienn; Gianolio, Eliana; Aime, Silvio; Baranyai, Zsolt
Abstract: Herein, the synthesis and an extensive characterization of two novel Gd(AAZTA) (AAZTA=6‐amino‐6‐methylperhydro‐1, 4‐diazepine tetra acetic acid) derivatives functionalized with short (C2 and C4 ) n ‐alkyl acid functions are reported. The carboxylate functionality is the site for further conjugations for the design of more specific contrast agents (CAs). Interestingly, it has been found that the synthesized complexes display enhanced properties for use as MRI contrast agents on their own. The stability constants determined by using potentiometric titration and UV/Vis spectrophotometry were slightly higher than the one reported for the parent Gd(AAZTA) complex. This observation might be accounted for by the larger sigma‐electron donation of the acyl substituents with respect to the one provided by the methyl group in the parent complex. As far as concerns the kinetic stability, transmetallation experiments with endogenous ions (e.g. Cu 2+ ) implied that the Gd 3+ ions present in these Gd(AAZTA) derivatives show somewhat smaller susceptibility to chemical exchange towards these ions at 25 °C, close to the physiological condition. The 1 H NMR spectra of the complexes with Eu III and Yb III displayed a set of signals consistent with half the number of methylene protons present on each ligand. The number of resonances was invariant over a large range of temperatures, suggesting the occurrence of a fast interconversion between structural isomers. The relaxivity values (298 K, 20 MHz) were consistent with q =2 being equal to 8.8 mm −1  s −1 for the C2 derivative and 9.4 mm −1  s −1 for the C4 one, that is, sensibly larger than the one reported for Gd(AAZTA) (7.1 mm −1  s −1 ). Variable‐temperature (VT)‐ T 2 17 O NMR measurements showed, for both complexes, the presence of two populations of coordinated water molecules, one in fast and one in slow exchange with the bulk water. As the high‐resolution 1 H NMR spectra of the analogs with Eu III and Yb III did not show the occurrence of distinct isomers (as frequently observed in other macrocyclic lanthanide(III)‐containing complexes), we surmised the presence of two fast‐interconverting isomers in solution. The analysis of the 17 O NMR VT‐ T 2 profiles versus temperature allowed their relative molar fraction to be established as 35 % for the isomer with the fast exchanging water and 65 % for the isomer with the water molecules in slower exchange. Finally, 1 H NMRD profiles over an extended range of applied magnetic field strengths have been satisfactory fitted on the basis of the occurrence of the two interconverting species. Abstract : The good properties of Gd(AAZTA) (AAZTA=6‐amino‐6‐methylperhydro‐1, 4‐diazepine tetra acetic acid) as a MRI contrast agent are further improved by simply attaching a short n ‐alkyl function on the ligand's surface. The variable temperature (VT)‐ T 2 measurements of the 17 OH2 resonance suggest the occurrence of two interconverting isomers in solution characterized by very different exchange rates of the coordinated water molecules.